Effects of methionine supplementation on the expression of protein deposition-related genes in acute heat stress-exposed broilers - Vesco, Ana Paula Del; Gasparino, Eliane; Grieser, Daiane Oliveira; Zancanela, Vittor; Voltolini, Débora Marques; Khatlab, Angélica Souza; Guimarães, Simone Eliza Facioni; Soares, Maria Amélia Menck; Neto, Adhemar Rodrigues Oliveira (Plos One, 2015)
The objective of this study was to evaluate the effect of heat stress and methionine supplementation on the gene expression of insulin-like growth factor I (IGF-I), growth hormone receptor (GHR), phosphatidylinositol 3-kinase, and regulatory 1 (PI3KR1) in the liver, as well as the expression of the atrogin 1 and cathepsin L2 (CTSL2) genes in the breast muscle of broilers. Broilers from 1–21 and 22–42 days of age were divided into three treatments related to methionine supplementation as follows: without methionine supplementation (MD), recommended level of methionine (DL1), and excess supplementation of methionine (DL2). The animals were either maintained at a thermal comfort temperature or exposed to heat stress (HS) (38°C for 24 hours, starting on day 20 or day 41 for experiments 1 and 2, respectively). The heat stress increased the body temperature at both ages. Starter period: The HS animals presented increased plasma creatinine content (P<0.0001) and the highest CTSL2 gene expression (P<0.0001). The methionine supplementation increased the IGF-I (P = 0.0144) and GHR (P = 0.0011) gene expression and decreased the CTSL2 (P = 0.0004) and atrogin 1 (P = 0.0012) gene expression. Grower period: Significant effects for the interaction between supplementation and environment were observed for GHR (P = 0.0252) and CTSL2 (P = 0.0011) gene expression. The highest GHR expression was observed in animals that remained in thermal comfort on the DL2 diet, and the lowest expression occurred in the HS animals fed the MD diet. For CTSL2, the HS animals fed the MD diet presented the highest CTSL2 gene expression, and the lowest expression was observed in the animals maintained at thermal comfort on DL1 and DL2 diets. Only methionine supplementation had effect on atrogin-1 gene expression (P<0.0001), with higher methionine content in the diet lower atrogin-1 gene expression was observed. Our results suggest that heat stress induces greater protein degradation and that methionine supplementation could induce protein deposition because methionine increased the expression of genes related to protein synthesis and decreased the expression of genes related to protein breakdown.
Keywords: Methionine supplementation; Protein; Broilers